PENGARUH MODEL PEMBELAJARAN DISKUSI KELAS DENGAN METODE SEMINAR SOCRATES TERHADAP HASIL BELAJAR SISWA MATERI KALOR KELAS X SMA NEGERI 8 MEDAN T.P 2013/2014 - Mutia Kemala Putri; Ridwan Abdullah Sani (UNIVERSITAS NEGERI MEDAN, 2015)
This study aims to determine the effect of classroom discussion learning model using Socratic seminar method to the student’s learning result in the heat topic of second semester X Class of SMA Negeri 8 Medan T.P 2013/2014. This research is quasi experimental with research design is Two Group Pretes-Postes Design. The population in this research was all students in class X which consists of 12 classes and the totaled is 343 students. Class X-8 and X-7 were chosen as an experimental class and control class with random sampling technique. Instrument learning results were contain of multiple-choice tests and observation sheet of student activity in the classroom. Average data of pre-test experimental class and control class are 44,33 and 40,33. In both classes, the pretest data are normally distributed and homogeneous. The ability of students at the beginning of both classes are same as analyzed by t-test. After treatment,the data of learning achievement using posttest, shows average yield of experimental class and control class are 70,17 and 56,50, which are normally distributed and homogeneous. Based on t-test, Ha was accepted and reveal that there is significant influence of classroom discussion learning model using Socratic Seminar method to the student learning outcomes. Keywords : classroom discussion, Socratic seminar, quasi experiment, learning results